Incentivizing older people to delay social security claiming - Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Given rising life expectations around the world, it seems that old-age pension benefits will need to be cut and pension contributions boosted in many nations. Yet our research on old-age system reforms does not require raising mandatory retirement ages or contributions. Instead, we offer ways to enhance incentives for people to work longer and delay retirement. There are good reasons to incentivize older people to work longer and delay retirement. These include rising longevity, the shrinking workforce, and emerging evidence indicating that working longer can be associated with better mental and physical health for many people. Nevertheless, old age Social Security systems in many nations find that people tend to claim benefits early, usually leading to reduced benefits. In the United States, for instance, a majority of Americans claim their Social Security benefits at the earlier feasible age, namely 62, even though their monthly benefits would be 75% higher if they waited until age 70. To test whether this is the result of people underweighting the economic value of higher lifetime benefit streams, we examine whether people would claim later and work longer if they were rewarded with a lump sum instead of a higher lifetime benefit stream for deferring. Two arguments have been offered to explain early claiming. One is that workers claim early to avoid potentially 'forfeiting' their deferred benefits should they die too soon (Brown et al., 2016). A second explanation is that many people underweight the economic value of lifetime benefit streams (Brown et al., 2017). This latter rationale motivates the present study.
urn:nbn:de:hebis:30:3-443131
Keywords: 330; pensions; German retirement system; social security claiming